Visualizing complex data for citizen education: a pedagogical workshop - Lopes, Renata Perim; Souto, Vitória; Kurkdjian, Valentina; Lorosa , Vinicius; Kosminsky, Doris (InfoDesign, 2025)
This article presents the Amplia Saúde Workshop, developed to engage non-specialist audiences with complex data visualizations on social and health issues originally created for researchers and health professionals. We asked whether such visualizations, when adapted for educational settings, could foster collective discussion and support critical data literacy. The workshop combined the scientific communication strategy with design thinking and was grounded in Freire-inspired critical pedagogy. Implemented with high school students in a public school in Rio de Janeiro, it used interactive visualizations from the Amplia Saúde platform together with activity booklets and teacher support materials. The results showed that students’ interest increased when data were contextualized within their own realities, that platform interaction required guided mediation to avoid misinterpretation, and that pedagogical materials were central in scaffolding comprehension. These findings indicate that complex visualizations, when critically mediated, can promote collective discussion, foster critical data literacy, and inform broader initiatives for lay adult audiences.